Environmental management of oil contaminated sites in Nigeria: improving policy and risk-based framework - Sam, Kabari Simeon (Cranfield University, 2016)
Contaminated land management has become a major concern for Nigeria. Sites affected by petroleum hydrocarbons from oil exploitation activities have been identified as a major environmental and socio-economic problem in the Niger Delta region. Though air and water regulations have received the most attention, the regulatory system for contaminated land remains largely undeveloped. As a result, Nigeria oil contaminated land governance lacks a clear and well-established policy framework; administrative structure and capacity; technical methods; and incentive structures. A consequence of these limitations is the inevitable ad hoc management of contaminated land in Nigeria. This thesis aims to provide a comprehensive and integrated contaminated land management policy framework for Nigeria. This work adopts a qualitative approach including critical review methodology and field surveys to investigate the current practice in contaminated land management in Nigeria. Key findings from this research clearly indicate an urgent need for a regulatory policy supported by a holistic and coordinated structure, coupled with improved technical capacity and additional resources to prevent new contamination and to address legacy contaminated sites. A technical strategy to identify and characterise contaminated land in terms of Source-Pathway-Receptor (S-P-R) linkages, a liability regime and the establishment of land use standards are required in Nigeria. Field surveys were used to pilot a proposed stakeholder engagement approach that integrates consideration of social values that could influence contaminated land management policy. Top ranked social values included drinking water, soil quality, and food and local supply chain. Based on this research a pathway for improving the current policy was proposed. The pathway identifies the need to engage stakeholders, educate and improve awareness, increase trust and transparency and integrate societal values into contaminated land management decision- making. An integrated risk assessment framework for contaminated land management in Nigeria was also proposed, and completed with a pathway for integrating the social values and sustainability indicators identified previously. The study proposes a timeline for achieving comprehensive contaminated land management policy in Nigeria. Finally, a multi-attribute methodology for contaminated land prioritisation in Nigeria was developed to identify and promptly respond to sites that pose the highest risk to receptors, considering the limited nature of resources for contaminated land management.
Keywords: Oil spill; risk-based; regulatory policy; sustainability; Niger Delta; prioritisation